Cross-Border Shopping of Czech Citizens Before, During, And After Covid Pandemic: A Quantitative Research - David MARTINCIK; Olga MARTINCIKOVA SOJKOVA (Communications of International Proceedings, 2023)
This paper delves into an examination of the determinants influencing cross-border shopping behavior among citizens of the Czech Republic. Specifically, the study scrutinizes the dynamic shifts in these determinants across three distinct temporal phases: pre-COVID, during the pandemic, and post-COVID. Employing a consistent methodology, we administered three identical questionnaires to gather comprehensive data during these periods. Throughout the investigation, it became apparent that the Czech Republic experienced a surge in inflation compared to its neighboring nations during the final period under consideration. The proportion of families engaging in cross-border shopping reached its nadir during the COVID period and attained its zenith in the aftermath of the pandemic. This nuanced trend is attributed to the economic repercussions of inflation, compelling many families to transition to international shopping practices. To elucidate these patterns, we employed ordinal logistic regression to assess two pivotal determinants influencing the frequency of cross-border shopping. The geographical distance between residents' abodes and international shopping venues emerged as a salient factor during the COVID period, reflecting heightened apprehensions about long-distance travel. However, this influence substantially waned post-COVID, as domestic inflation rendered cross-border shopping exceptionally advantageous. Furthermore, the significance of family size was pronounced in the pre-COVID era, with larger families exhibiting a proclivity for cross-border shopping. Notably, this correlation diminished during and post-COVID, indicating a leveling effect across family sizes. In summary, families of varying sizes exhibited comparable cross-border shopping frequencies during each period, with a discernible decline during the COVID era and a subsequent resurgence post-pandemic.
Keywords: Czech economic issues; shopping abroad determinants; shopping and inflation; shopping before; during and after COVID